2010
DOI: 10.2320/matertrans.m2009319
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Kinetic Parameters for Combustion Synthesis of FeAl Intermetallic Compound by Dipping Experiment of Fe Wire into Al Melt

Abstract: The formation reaction rate of Fe-Al intermetallic compounds was examined by dipping experiment of Fe wire into Al melt in the temperature range between 973 K and 1373 K, to determine the kinetic parameters of combustion synthesis of FeAl. A piece of Fe wire and Al powder were put into an alumina crucible, and vacuum-sealed in a quartz tube. The tube was held in an electric furnace to promote the compound formation reaction. A microstructure observation and SEM-EDX analysis of the dipped Fe wire were performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 17 publications
0
6
0
1
Order By: Relevance
“…[6] then describe even a FeAl 3 / Fe 2 Al 5 / FeAl 2 / FeAl sequence, beginning at the temperature lower than 600 C. On the other hand, Hibino at al. [22] stated that aluminium melts before the formation of intermetallics. After that, Fe 2 Al 5 , Fe 2 Al 3 and FeAl phases are gradually formed.…”
Section: Introductionmentioning
confidence: 99%
“…[6] then describe even a FeAl 3 / Fe 2 Al 5 / FeAl 2 / FeAl sequence, beginning at the temperature lower than 600 C. On the other hand, Hibino at al. [22] stated that aluminium melts before the formation of intermetallics. After that, Fe 2 Al 5 , Fe 2 Al 3 and FeAl phases are gradually formed.…”
Section: Introductionmentioning
confidence: 99%
“…This is because aluminum contained in the shot particle surfaces was transferred to the surface of the specimen during the FPP process. 14,19) The thickness of the Al transfer layer was approximately 20 μm, and was the same for all specimens. This means that the amount of transferred Al was almost the same in each case due to the same peening time being used.…”
Section: Characterization Of the Surface Modified Layermentioning
confidence: 99%
“…This trend is similar to that of the results of a previous study wherein the same treatment was performed for titanium alloy, and an aluminum transferred layer and a Ti-Al intermetallic compound layer were formed on the titanium alloy surface after FPP without subsequent heating. 14) The formation of the compound layer at a relatively low heating temperature within a short span of time during AIH-FPP is attributed to the occurrence of a combustion synthesis reaction between Fe and Al 20) and to the local increase in the temperature of the treated surface. 13) According to the XRD data (Fig.…”
Section: Mechanism Of the Surface Modified Layer Formation By Aih-fppmentioning
confidence: 99%
“…To take advantage of these properties, dissimilar materials need to be combined and this poses certain problems for their joining. Haddadi (2014), Yin et al (2013) and Hibino (2010) demonstrated that high temperature is a crucial factor in the formation of brittle intermetallic compounds. Solid-state welding processes have been developed to avoid the formation of these brittle compounds.…”
Section: Introductionmentioning
confidence: 99%